Association between Maternal Body Mass Index and Preeclampsia Incidence: Evidence from Bantul Hospital, Indonesia - Nur Baity Darojat; Dhesi Ari Astuti (The Indonesian Institute of Science and Technology Research, 2026)
Preeclampsia remains one of the leading causes of maternal mortality worldwide and is closely associated with several risk factors, particularly obesity. According to the World Health Organization, preeclampsia affects approximately 2–8% of pregnancies globally and contributes substantially to maternal deaths. In Indonesia, preeclampsia accounts for around 25% of maternal mortality cases. In Bantul Regency, the number of preeclampsia cases increased significantly from 161 cases in 2023 to 320 cases in 2024. Obesity is recognized as an important risk factor that can increase the likelihood of preeclampsia, while Body Mass Index (BMI) is widely used to assess maternal nutritional status. However, evidence regarding the relationship between BMI and preeclampsia at PKU Muhammadiyah Bantul Hospital is still limited. This study aimed to determine the association between BMI and the incidence of preeclampsia among mothers giving birth at PKU Muhammadiyah Bantul Hospital during 2024–2025. This study employed an observational analytical design with a case-control approach. A total of 322 respondents were selected through purposive sampling using complete medical record data. Data analysis was conducted using the Chi-Square test and Odds Ratio (OR). The results showed a significant relationship between BMI and preeclampsia incidence (p = 0.001). Obese mothers were found to have a substantially higher risk of developing preeclampsia compared with non-obese mothers (OR = 48.450; 95% CI: 22.578–103.967). These findings emphasize the importance of routine BMI screening during antenatal care for early detection and prevention of preeclampsia.